Using nature-based citizen science initiatives to enhance nature connection and mental health - Oh, Rachel R. Y.; Suarez-Castro, Andres F.; Fuller, Richard A.; Tervo, Michael; Rozario, Kevin; Peters, Birte; Chowdhury, Shawan; von Gönner, Julia; Friedrichs-Manthey, Martin; Berger, Ambros; Schultz, Tracy; Dean, Angela J.; et al. (Frontiers in Environmental Science, 2025)
The global rise in mental health issues underscores the critical importance of assessing the mental health benefits of engaging with nature. Beyond their primary aim of involving citizens in scientific data collection, nature-based citizen science initiatives offer significant potential for enhancing outcomes related to conservation (e.g., connection to nature) and human health and wellbeing (e.g., emotions, depression, stress, anxiety). However, the effectiveness of various types of initiatives in achieving specific outcomes remain unclear. This study evaluates changes in eight outcomes related to nature connection and health and wellbeing before and after participation in five initiatives in Australia and Germany. These initiatives varied in ecosystem type (urban parks, terrestrial forests and freshwater streams) and the participation duration (from 15 min to 48 h). We assessed three dimensions of connection to nature (Self, Experience and Perspective) measured by the Nature-Relatedness scale, mental health outcomes (symptoms of depression, stress and anxiety) using the DASS-21 scale, and emotional states (positive and negative emotions) using the Scale of Positive and Negative Experience (SPANE). We found that while participants generally reported improvements across all measured outcomes, only participation in the Queensland Trust for Nature initiative, characterized by its extended duration and social interactions, demonstrated statistically significant enhancements in mental health and emotions after controlling for socio-economic confounders. These findings suggest that while short-term nature-based interventions can effectively alleviate anxiety and stress symptoms and boost emotions, significant changes in nature connection and depression may require more intensive interventions than what is available through typical citizen science experiences. We advocate for reframing nature-based initiatives as integral components of broader health-promoting strategies. By aligning citizen science efforts with health promotion frameworks, these initiatives can achieve greater impact and simultaneously advance scientific understanding, support conservation strategies while improving human health.